(untitled) (Research, Society and Development, 2025)
Self-medication consists of the use of medications without proper prescription or professional guidance, a common practice among university students that can interfere with biochemical tests. The present study aimed to analyze, through an integrative literature review, the practice of self-medication among university students and its possible interferences in biochemical examinations. The research was conducted in the BVS, SciELO, CAPES, and NIH databases, using Portuguese and English descriptors related to self-medication, laboratory tests, and public health. Duplicate articles, those outside the topic, or those that did not meet the inclusion criteria were excluded. Of the 38 studies found, 12 met the criteria and were selected for analysis. The results showed that the most commonly used medications among university students were analgesics, antipyretics, and anti-inflammatory drugs. It was observed that the indiscriminate use of these drugs can interfere with biochemical parameters, compromising the interpretation of laboratory tests and masking clinical conditions. It is concluded that self-medication among university students has become an increasingly frequent practice, driven by the ease of access to medications, self-confidence in self-diagnosis, and lack of time to seek medical care.